Self-Ratings of Olfactory Performance and Odor Annoyance Are Associated With the Affective Impact of Odor, but Not With Smell Test Results. (March 2017) - Knaapila, Antti; Raittola, Auri; Sandell, Mari; Yang, Baoru
Our aim was to explore factors potentially associated with subjective (self-rated) and objective (measured using the Sniffin' Sticks Extended test) olfactory performance in the general population without olfactory disorders. We studied associations between olfactory performance and how important odors were in determining liking for new places, things, and people (measured using the Affective Impact of Odor scale) and the average annoyance caused by odors in 117 adults (83 women, 34 men; age 18–69 years, mean age 32 years). In a subset of 44 participants, we also studied associations between olfactory performance and spice odor identification task scores (14 odors) and the number of herbs and spices consumed. Self-rated olfactory acuity and odor-related annoyance were associated with the Affective Impact of Odor scores, but neither correlated with the smell test results. Instead, the number of spices consumed correlated with spice odor identification score ( r = .50) and the identification (but not threshold nor discrimination) subscore of the Sniffin' Sticks test ( r = .49). Our results suggest that a tendency to perceive odors in affective terms may be associated with overestimation of olfactory abilities and that recurrent exposure to a large variety of spice odors may improve performance on odor identification.